Associação entre a orientação da atenção primária à saúde e o uso de serviços odontológicos no Brasil - Mozzaquatro, Caroline Desconsi (2023)
Primary Health Care (PHC) represents the gateway to health services for a large part of the population, and its use represents effective access, a result of the behavior of the individual seeking care and also, the characteristics of the service. In addition, it plays a role in coordinating health actions, structuring services in care networks, according to the needs identified in the community. Thus, the aim of this research was to evaluate the prevalence of the use of dental services in the last 12 months and its association with the presence and extent of PHC attributes. This a cross-sectional study and used data collected in the second edition of the National Health Survey (NHS), carried out in 2019, having as inclusion criteria individuals aged 18 years or older, who answered the questions in module H (Medical Care) and obtained a score of 1 for question H4, that is, users who sought medical care provided in Basic Health Units. The PCATool (Primary Care Assessment Tool) was used to measure the orientation of the PHC and the control variables were based on previous studies and include area of residence, gender, age, self-reported skin color, education and wealth, organized into categories. Data were analyzed descriptively, and a logistic regression analysis was used to find crude and adjusted associations between variables and use of dental services (CI=95%). A total of 9,396 people were included in the analysis, the majority being adults (18-59 years old), female and residents of the urban area. Less than half reported having used the dental service in the last 12 months (47.5%). A greater chance of using dental services in the last twelve months was observed in health services with high PHC orientation (OR 1.32 95%CI: 1.13-1.45), even after controlling for demographic and socioeconomic variables ( p<0.0001).